2022
DOI: 10.1039/d2ta03161b
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable CFRPs with extremely high Tg: hydrothermal recyclability in pure water and upcycling of the recyclates for new composite preparation

Abstract: In recent years researchers have introduced different malleable and/or degradable thermosetting polymers to address the recyclability of traditional thermoset materials. Nonetheless, the mechanical properties and glass transition temperature (Tg) of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Tan (delta) versus temperature curves (a), DSC curves (b), and TGA curves (c) for the EPOXY-ASCs and EPOXY-MXDA-5. Comparison of the mechanical properties and thermal performance with other high-performance dynamic cross-linked epoxy resins reported in literature studies (d). ,,,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Tan (delta) versus temperature curves (a), DSC curves (b), and TGA curves (c) for the EPOXY-ASCs and EPOXY-MXDA-5. Comparison of the mechanical properties and thermal performance with other high-performance dynamic cross-linked epoxy resins reported in literature studies (d). ,,,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Hao et al. reported an epoxy thermoset based on tetraglycidyl methylenedianiline ( TGDDM ), nadic methyl anhydride ( NMA ), and triethanolamine [65] . The network was synthesized in bulk with a three‐step heating process, consisting of 1 h at 130 °C, followed by 1 h at 170 °C, and finally 1 h at 220 °C.…”
Section: Classification Of Recyclable Epoxy Thermosetsmentioning
confidence: 99%
“…[83] In addition, it was shown that, while the recycled carbon fibers through thermal recycling can largely maintain their reinforcement capabilities, the recycled glass fibers can be significantly damaged with the reduction of at least 50% strength. [84] For chemical recycling, the most conventional process is solvolysis [85][86][87][88][89][90] which leverages a wide range of solvents for the degradation or depolymerization of matrices to recycle fibers (Figure 3D). Several studies showed that the tensile strength of recycled fibers can be maintained with at least 90% of the original fibers.…”
Section: Global Production Of Polymers Demand Wastementioning
confidence: 99%
“…[ 72 ] Thermal and chemical recycling were exemplified by (C) pyrolysis and oxidation of used and hardened CFRPs [ 77 ] and (D) solvolysis of used and hardened CFRPs with different solvents. [ 86,90 ] (E) Thermoplastic PPCs or PFRPs. VARTM, vacuum assisted resin transfer molding…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation